2001
DOI: 10.1007/s10157-001-8014-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of apolipoprotein E variants in lipoprotein glomerulopathy and other renal lipidoses

Abstract: Lipoprotein glomerulopathy (LPG) is a new renal lipidosis entity, characterized by peculiar histology and abnormal lipoprotein profiles mimicking type III hyperlipoproteinemia. Recently, it has been clarified that LPG is associated with novel apolipoprotein E (apoE) mutations. In particular, ApoE-Sendai, which substitutes arginine 145 with proline, is observed in most Japanese patients with LPG, although isoelectric focusing polyacrylamide gel electrophoresis has shown that it is consistent with the apoE2 isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Some cases with specific renal lesions for LPG showed normal lipid profile [2,16]. Therefore, LPG is considered not to be caused by hyperlipoproteinemia due to reduced LDL receptor binding capacity by apoE variants, but to be caused by specific deposition of abnormal lipoproteins including apoE variants in the kidneys [10,17]. From this point of view, renal histology, especially electron microscopy [18] and lipid staining [19], is the most reliable diagnostic tool for LPG.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some cases with specific renal lesions for LPG showed normal lipid profile [2,16]. Therefore, LPG is considered not to be caused by hyperlipoproteinemia due to reduced LDL receptor binding capacity by apoE variants, but to be caused by specific deposition of abnormal lipoproteins including apoE variants in the kidneys [10,17]. From this point of view, renal histology, especially electron microscopy [18] and lipid staining [19], is the most reliable diagnostic tool for LPG.…”
Section: Introductionmentioning
confidence: 97%
“…An apoE variant, Apo E2(Arg145Pro) Sendai, was initially identified [4], and subsequently several other variants were also discovered in LPG patients [5][6][7][8][9]. These evidences have indicated that abnormal apoE is responsible for LPG [2,10], and that the structural changes of the binding site with lowdensity lipoprotein (LDL) receptor, 140-150 residues of apoE, result in type III hyperlipoproteinemia [5,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was suggested that the ApoE mutations, ApoE Sendai, ApoE Tokyo and ApoE1 resulted in inefficient receptor binding and increased lipid, lipoprotein and ApoE levels. In general, however, LPG has not been associated with the extra-renal manifestation of hyperlipoproteinaemia and hyperlipidaemia, such as arteriosclerosis and xanthoma [3]. In patients with LPG, the presence of lipoprotein thrombi in almost all glomeruli, the absence of foam cells and elevated ApoE level were typical features [2].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been reported that ApoE mutations, ApoE Sendai (Arg 145 Pro), ApoE Kyoto (Arg 25 Cys), ApoE Tokyo/Maebashi (3 amino acid deletion, residues 141 to 143) and ApoE1 (18 amino acid deletion, residues 156 to 173) are associated with LPG [3]. ApoE has a major role in the metabolism of lipids and lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation